NURSE’S ROLE IN THE CONTROL OF ARTERIAL HYPERTENSION AND MORBIMORTALITY FACTORS IN THE ELDERLY - Anjos, Andréa dos Santos dos; Silva, Francine Bontorin da; Nascimento, Kátia Fialho do; Souza, Silvia Jaqueline Pereira de (Health and Society, 2023)
Arterial hypertension is a non-communicable, asymptomatic chronic disease that is entirely linked to the high rates of morbidity and mortality that affect the quality of life of the elderly. We seek to understand how arterial hypertension can be treated to reduce the number of deaths in elderly people and describe the role of the nursing team in controlling arterial hypertension. This is an integrative review established by Cooper, the searches took place in the Virtual Health Library and Pubmed, using the descriptors “hypertension”, “nurse”, “prevention”, “mortality associated with each other by the Boolean operator “and”, in the period from 2016 to 2021, resulting in the initial search of 972 articles that after applying the selection criteria and reading in full, 38 remained that made up the research corpus. The socio-environmental and genetic conditions, which when related to senescence and unhealthy life habits, imply the triggering of hypertension, a health problem with loss of quality of life and increased morbidity and mortality. Nursing professionals who work in primary care are the crucial link in the early detection and development of actions aimed at health care, aiming to control the blood pressure levels of patients affected by AH, disseminating information aimed at health education.